The Impact of Hazardous and Toxic Waste (B3) Transportation on the Environment at the West Pasaman General Hospital - Muhelni, Leila; Pariza, Nanda; Annisa, Indah Febri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
Hazardous and toxic waste is the residual waste from any business or activity that contains hazardous and toxic materials. According to the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia No. P.56 of 2015, hospitals are categorized as healthcare facilities required to manage B3 waste. The importance of managing hazardous and toxic waste in hospitals is significant, as improper management can lead to various negative impacts.In the transportation of B3 waste, RSUD Pasaman Barat collaborates with PT. Andalas Bumi Lestari, conducting transport twice a month. The aim of this research is to calculate the emissions of CO₂, CH₄, and N₂O from the transportation activities occurring at the Temporary Storage Site (TPS) of RSUD Pasaman Barat. This study seeks to understand the impact of hazardous waste transportation on global warming at RSUD Pasaman Barat. This research employs a quantitative method to calculate emissions from the transportation activities of hazardous and toxic waste at RSUD Pasaman Barat.